COGNITIVE GENRE PROTOTYPE MODELLING AND ITS IMPLICATIONS FOR THE TEACHING OF ACADEMIC WRITING TO LEARNERS OF ENGLISH AS A SECOND LANGUAGE - Jamilova Gulshodabonu; Ubaydullayeva Muattar Urinbekovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The teaching of academic writing to learners of English as a second language has long been preoccupied with two competing concerns: faithful reproduction of the formal conventions of established scholarly genres, and the development of learner agency and rhetorical creativity. This paper proposes an integrative theoretical framework — Cognitive Genre Prototype Modelling (CGPM) — that draws on Eleanor Rosch’s prototype theory, John Swales’ move-step analysis, and contemporary cognitive accounts of genre to reconceptualise genre knowledge as a structured mental representation organised around prototypical exemplars rather than rigid sets of necessary and sufficient features. The study reports findings from an eight-week pedagogical intervention conducted with thirty intermediate-level ESL learners enrolled in a university-based English for Academic Purposes (EAP) programme, and contrasts these outcomes with those of a comparable control group receiving conventional genre-based instruction. Analytic comparison of pre- and post- intervention texts, supplemented by questionnaire data and semi-structured interviews, indicates that learners exposed to CGPM demonstrated stronger rhetorical structuring, greater discoursal flexibility, and an enhanced metacognitive vocabulary for describing their own writing decisions. The paper concludes by outlining implications for syllabus design, materials development, teacher education, and the assessment of academic writing in second-language settings.